Morphometric and genetic characterization as tools for selection of Apis mellifera (Hymenoptera: Apidae) stocks in an area of natural hybridization in Argentina - Litvinoff, Leonardo; Menescardi, Francisco; Porrini, Leonardo; Russo, Romina; Liendo, María Clara; Nucci, Alejandro; Lusarreta, Esteban; Ventura, Rocio; Espasadin, Luna; Monmany-Garzia, A. Carolina; Scannapieco, Alejandra C.; Galindo-Cardona, Alberto (Frontiers in Insect Science, 2023)
Beekeepers around the world select bees’ characteristics that facilitate and favor production. In regions where hybridization among lineages is taking place, this selection is a challenge, given that these regions are "natural laboratories", where the action of evolutionary processes of a population or species occurs in real time. A natural honeybee (Apis mellifera) hybrid zone exists in Argentina between 28º and 35º South, where Africanized (AHB) and European (EHB) populations converge. In this zone, beekeepers use selected genetic resources of European origin mostly, since the local Africanized bees show a higher defensive behavior, which is not desirable for management. Although EHB colonies have many advantages for honey production, they are not fully adapted to the subtropical climate and are susceptible to certain parasitosis such as varroosis. In addition, both AHB and EHB mate in drone congregation areas (DCAs), where males and virgin queens fly to meet, resulting in variability in the desired characteristics. In this study, we explored the degree of hybridization within a DCA and its reference apiary, located in the province of Entre Ríos, by applying two complementary techniques. First, morphotypes with different degrees of hybridization between European and African subspecies were observed in the reference apiary, indicating a high sensitivity of this morphometric approach to detect hybridization in these populations. Second, a genetic analysis revealed haplotypes of both origins for drones in DCAs, with a higher prevalence of European haplotypes, while all the colonies from the reference apiary exhibited European haplotypes. Overall, our results are in line with the strong impact that commercial beekeeping has on the genetics of DCAs. We show how wing morphometry may be used to monitor hybridization between European and African subspecies, a tool that may be evaluated in other regions of the world where hybridization occurs.